Lining the nest with more feathers increases offspring recruitment probability: Selection on an extended phenotype in the blue tit - Pauliina Järvinen; Jon E. Brommer (WILEY, 2022)
Birds, among various other taxa, construct nests. Nests form an extended phenotype of the individual building it. Nests are used to extend control over the conditions in which offspring develop, and are therefore commonly considered to be shaped by selection. Nevertheless, scarcely any scientific evidence exist that nest composition is under selection. Here, we demonstrate with data from over 400 blue tit (Cyanistes caeruleus) nests collected over 8 years that a higher proportion of feathers in the nest lining is positively associated with the probability of offspring to recruit as a breeding adult later in life. Strikingly, the extended phenotype (nest) was associated stronger with recruitment probability than phenotypic traits that have typically been considered important in selection (laying date, and female size and condition). Our findings suggest that the choice of nest material could be a maternal behavior with potential lifelong effects on her offspring.